DEVELOPMENT OF LEARNING MEDIA BASED ON FOCUSKY APPLICATIONS ON THE STRUCTURE AND FUNCTIONS OF PLANT TISSUE - Winda Sari Angliani; M Mellisa (Universitas Negeri Medan, 2022)
This study aims to produce a Focusky application-based learning media on the material structure and function of valid plant tissues. This research uses the Research and Development (R&D) method and the ADDIE model. Data were obtained by validating learning media to media experts, material experts, and teachers and looking at student response questionnaires to the media developed by conducting limited validity trials. The validation results by media experts showed an average of 92.5% (very valid). The results of material expert validation get an average of 93.33% (very valid). The validation results by three teachers who teach Biology subjects get an average of 96% (very valid). The students' responses from the three schools averaged 93.9% (very good). Based on the validation results from experts, biology teachers, and student responses, it was found that the learning media product based on the Focusky application on the material structure and function of plant tissue was categorized as very valid for use in learning.